2020
DOI: 10.3390/nu12030712
|View full text |Cite
|
Sign up to set email alerts
|

Social Stratification, Diet Diversity and Malnutrition among Preschoolers: A Survey of Addis Ababa, Ethiopia

Abstract: In Sub-Saharan Africa, being overweight in childhood is rapidly rising while stunting is still remaining at unacceptable levels. A key contributor to this double burden of malnutrition is dietary changes associated with nutrition transition. Although the importance of socio-economic drivers is known, there is limited knowledge about their stratification and relative importance to diet and to different forms of malnutrition. The aim of this study was to assess diet diversity and malnutrition in preschoolers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 48 publications
(59 reference statements)
2
43
0
1
Order By: Relevance
“…In the urban settings, the rate of malnutrition among underfive children was persistently higher, and the nutrition transition phenomenon impacted the health of children in which the rate of obesity has been radically progressed and that ultimately attributed to many lifethreatening non-communicable diseases including dietrelated cardio-metabolic risk and cancer [6,23,24]. The prevalence of chronic undernutrition in these urban settings was much higher than from studies conducted in urban settings of Ethiopia in Arba Minch (18.7%) [25], Addis Ababa (19.6%) [17], Kersa district (8.9%) [26], rural Kenya (32%) [27], South Africa (35%) [28], and urban cities of South Africa, Umlazi (28%), Rietvlei (20%), and Paarl (17%) [4]. However, it was less than the findings in rural and pre-urban areas in Ethiopia such as Humbo districts (75%) [29], Merhabete district (52.4%) [30], Libo-kemekem district (49.4%) [31], and Lalibela town (47.3%) [32].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the urban settings, the rate of malnutrition among underfive children was persistently higher, and the nutrition transition phenomenon impacted the health of children in which the rate of obesity has been radically progressed and that ultimately attributed to many lifethreatening non-communicable diseases including dietrelated cardio-metabolic risk and cancer [6,23,24]. The prevalence of chronic undernutrition in these urban settings was much higher than from studies conducted in urban settings of Ethiopia in Arba Minch (18.7%) [25], Addis Ababa (19.6%) [17], Kersa district (8.9%) [26], rural Kenya (32%) [27], South Africa (35%) [28], and urban cities of South Africa, Umlazi (28%), Rietvlei (20%), and Paarl (17%) [4]. However, it was less than the findings in rural and pre-urban areas in Ethiopia such as Humbo districts (75%) [29], Merhabete district (52.4%) [30], Libo-kemekem district (49.4%) [31], and Lalibela town (47.3%) [32].…”
Section: Discussionmentioning
confidence: 90%
“…All children aged between 6 and 59 months that have resided in the study area for the last 6 months were included in the study sample, while any child with a severe medical problem, lack of household head or caregivers, or physical deformity was excluded from the study. The largest sample (512 mother-child pairs) was taken from a study conducted in Ethiopia by considering maternal education as a predictor for child stunting and overweight [ 17 ] with the assumptions that 95% of confidence level, 80% of power, 1.7 the odds of being stunting when the mother is not educated, and 24.3% of child stunting among uneducated mothers. Three sub-cities from Dessie and two kebeles from Combolcha town were selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…According to the framework, the basic causes including poverty, social condition, and political, economic, ecological, and other factors were the root reason for any form of malnutrition [13]. Different literature studies explicitly identified sociodemographic factors that were highly correlated with obesity, for example, older age [2,6], married (marital status) [14], low wealth index [6,10,[15][16][17], urban residency [6,10,16,18], being female [2,9], learning in private schools [2,9,19,20], easy accessibility of junk and fired or energy-dense foods and packed animal source foods due to free trade policy [2], rural to urban migration, replacement of local agribusiness with food retail [21], higher education level [6,7,22], and being pregnant [6,18]. In contrary to the previous findings, a study conducted among French women shows that having a higher income, a higher occupational class, and a higher educational level and having hot water at home reduce the occurrence of obesity [23] although the pathophysiology of hot water at home and obesity occurrence was not yet studied.…”
Section: Sociodemographic Factors Based On United Nationsmentioning
confidence: 99%
“…In the Infant and Young Child Feeding guidelines published by the United Nations, dietary diversity scores of pre-school children are dichotomized: children who had at least four of the seven food groups were considered to have adequately diversi ed dietary intake [29]. In our study, we dichotomized the score using median as there is no recommended cut-off points for our study population (school-age children) [16][17][18][19][20][21]. The median of the children's dietary diversity scores was calculated to determine the cutoff point between lower and higher dietary diversity.…”
Section: Data Management and Statistical Analysismentioning
confidence: 99%
“…Along with micronutrient supplementation, su cient dietary diversity is considered a key to improving overall nutritional and health status of children living with HIV [12][13][14]. A number of recent studies have explored risk factors for undernutrition, using dietary diversity score developed by the Food and Agriculture Organization [15][16][17][18][19][20]. Dietary diversity score, which consists of a simple count of food groups that an individual has consumed over the preceding 24 hours, is considered a proxy for nutrient adequacy of the diet of individuals [21].…”
Section: Introductionmentioning
confidence: 99%